Treatment of Nonvariceal Gastrointestinal Hemorrhage by Transcatheter Embolization. (13th June 2013) - Ali, Muhammad; Ul Haq, Tanveer; Salam, Basit; Beg, Madiha; Sayani, Raza; Azeemuddin, Muhammad
Abstract : Purpose . To investigate the sensitivity of mesenteric angiography, technical success of hemostasis, clinical success rate, and complications of transcatheter embolization for the treatment of acute nonvariceal gastrointestinal hemorrhage. Material and Methods . A retrospective review of 200 consecutive patients who underwent mesenteric arteriography for acute nonvariceal gastrointestinal hemorrhage between February 2004 and February 2011 was done. Results . Of 200 angiographic studies, 114 correctly revealed the bleeding site with mesenteric angiography. 47 (41%) patients had upper gastrointestinal hemorrhage and 67 (59%) patients had lower gastrointestinal hemorrhage. Out of these 114, in 112 patients (98%) technical success was achieved with immediate cessation of bleeding. 81 patients could be followed for one month. Clinical success was achieved in 72 out of these 81 patients (89%). Seven patients rebled. 2 patients developed bowel ischemia. Four patients underwent surgery for bowel ischemia or rebleeding. Conclusion . The use of therapeutic transcatheter embolization for treatment of acute gastrointestinal hemorrhage is highly successful and relatively safe with 98% technical success and 2.4% postembolization ischemia in our series. In 89% of cases it was definitive without any further intervention.